2006
DOI: 10.1038/sj.ejcn.1602466
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, fitness and health in Taiwanese children and adolescents

Abstract: Objective: To examine the prevalence of childhood and adolescent obesity in Taiwan and investigate the association between excess weight and physical fitness and blood pressure. Design: Cross-sectional study. Subjects: A total of 13 935 children and adolescents aged 6-18 years (boys: 7031, girls: 6904) were involved in the 1999 survey and 24 586 (boys: 12 367, girls: 12 219) were available in the 2001 survey. Measurements: Weight, height, systolic and diastolic blood pressures, and health-related fitness tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
72
2
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 46 publications
30
72
2
11
Order By: Relevance
“…[1][2][3][4][5] In high-income countries, this trend was associated with a shift in upper parts of the body mass index (BMI) distribution rather than with a shift in the BMI distribution in the whole population. [6][7][8][9] If a risk factor particularly affects children with high BMI and the exposure frequency of this risk factor has increased over time within a population, an increase in upper BMI percentiles could be explained.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In high-income countries, this trend was associated with a shift in upper parts of the body mass index (BMI) distribution rather than with a shift in the BMI distribution in the whole population. [6][7][8][9] If a risk factor particularly affects children with high BMI and the exposure frequency of this risk factor has increased over time within a population, an increase in upper BMI percentiles could be explained.…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, China the prevalence of overweight during childhood almost doubled between 1986 (13%) and 2009 (27.7%) 7 . Also, a study conducted in the United States revealed that 31.8% of the children between 2 and 19 were overweight or obese 8 .…”
mentioning
confidence: 99%
“…Con lo cual, la obesidad se convirtió en el quinto factor de riesgo de muerte en el mundo, representando una amenaza creciente para la salud tanto en países desarrollados como en vías de desarrollo (2) .…”
Section: Introductionunclassified